2002
DOI: 10.1007/s00572-002-0171-z
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza-induced differential response to a yellows disease in tomato

Abstract: The protective effects induced by arbuscular mycorrhizal (AM) fungi against a phytoplasma of the Stolbur group have been investigated in tomato by morphometry and flow cytometry. Symptoms induced by the phytoplasma were less severe when the plants also harboured AM fungi. Morphological parameters such as shoot and root fresh weight, shoot height, internode length, leaf number and adventitious root diameter were closer to those of healthy plants when arbuscular mycorrhiza were present. Reduced nuclear senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(46 citation statements)
references
References 42 publications
(38 reference statements)
4
42
0
Order By: Relevance
“…L. asiaticusinfected citrus were reduced after the application of Pi. In the case of phytoplasmas, although the correlation between Pi and the disease symptoms remains unclear, the disease symptoms in phytoplasma-infected plants could be reduced by the application of AM fungi (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012). AM fungi are symbiotic organisms that are able to enhance the uptake of Pi through up-regulation of Pi starvation responses in host plants (Branscheid et al, 2010;Gu et al, 2010;Volpe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. asiaticusinfected citrus were reduced after the application of Pi. In the case of phytoplasmas, although the correlation between Pi and the disease symptoms remains unclear, the disease symptoms in phytoplasma-infected plants could be reduced by the application of AM fungi (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012). AM fungi are symbiotic organisms that are able to enhance the uptake of Pi through up-regulation of Pi starvation responses in host plants (Branscheid et al, 2010;Gu et al, 2010;Volpe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Colonization by AM fungi can modify the plants' root architecture and enhance the uptake of mineral nutrients, in particular Pi (Gu et al, 2011;Volpe et al, 2013). Interestingly, several studies also reported that AM fungi reduce the disease symptoms caused by phytoplasmas (Lingua et al, 2002;Romanazzi et al, 2009;Kami nska et al, 2010;Sampò et al, 2012).…”
mentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi (AMF) form associations with the roots of the vast majority of land plants; the fungus colonizes the roots and forms arbuscules within root cortical cells thus improving plant nutrient uptake, especially phosphorus (Smith & Read 1997). Moreover, increasing evidence shows that symbiotic fungi contribute to plant adaptation to multiple biotic and abiotic stresses (Gohre & Paszkowski 2006, Lebeau et al 2008, Lingua et al 2002, Liu et al 2007, Rodriguez & Redman 2008, Smith et al 2010). In the case of HMs, the beneficial ef-fect varies according to plant and fungal species, metal and concentration (Bois et al 2005, Lebeau et al 2008, Takacs et al 2005, Todeschini et al 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, several studies have observed a positive effect of the symbiosis on plant resistance to other shoot pathogens. In tomato, AM reduced disease symptoms caused by a phytoplasma and conferred protection against the necrotrophic fungus Alternaria solani (Lingua et al 2002 ;Fritz et al 2006 ;de la Noval et al 2007) . Similarly, colonisation by Glomus mosseae reduces disease symptoms and proliferation of Pseudomonas syringae in tomato leaves (J. García-Andrade and M.J. Pozo, unpublished results).…”
Section: Mycorrhiza-induced Resistance Against Pathogensmentioning
confidence: 99%